The problem of pulmonary arterial hypertension in end-stage renal disease: can peritoneal dialysis be the solution - Abdullah K. Alhwiesh; Ibrahiem Saeed Abdul-Rahman; Abdullah Alshehri; Amani Alhwiesh; Mahmoud Elnokeety; Syed Essam; Mohamad Sakr; Nadia Al-Oudah; Abdulla Abdulrahman; Abdelgalil Moaz Mohammed; Hany Mansour; Tamer El-Salamoni; et al. (BMC Nephrology, 2022)
Abstract Background Pulmonary arterial hypertension (PAH) in the setting of end-stage renal disease (ESRD) has important prognostic and therapeutic consequences. We estimated the prevalence of PAH among patients with ESRD treated with automated peritoneal dialysis (APD), investigated the effect of different variables and compared pulmonary artery pressure and cardiac function at the beginning and end of the study. Methods This is a 5-year study in which 31 ESRD patients on APD were recruited after fulfilling inclusion criteria. Blood samples were collected from all patients for the biochemical and hematological data at the beginning of the study and every month and at the study termination. Total body water (TBW) and extracellular water (ECW) were calculated using Watson’s and Bird’s calculation methods. All patients were followed-up at 3-month interval for cardiac evaluation. Logistic regression analysis was used to assess the relation between different variables and PAH. Results The mean age of the study population (n = 31) was 51.23 ± 15.24 years. PAH was found in 24.2% of the patients. Mean systolic pulmonary artery pressure (sPAP) and mean pulmonary artery pressure (mPAP) were significantly higher in the APD patients at study initiation than at the end of the study (40.75 + 10.61 vs 23.55 + 9.20 and 29.66 + 11.35 vs 18.24 + 6.75 mmHg respectively, p = 0.001). The median ejection fraction was significantly lower in patients with PAH at zero point than at study termination [31% (27-34) vs 50% (46-52), p = 0.002]. Hypervolemia decreased significantly at the end of study (p <  0.001) and correlated positively with the PAP (r = 0.371 and r = 0.369), p = 0.002). sPAP correlated with left ventricular mass index, hemoglobin level, and duration on APD. Conclusions Long term APD (> 1 years) seemed to decrease pulmonary arterial pressure, right atrial pressure and improve left ventricular ejection fraction (LVEF). Risk factors for PAH in ESRD were hypervolemia, abnormal ECHO findings and low hemoglobin levels. Clinical and echocardiographic abnormalities and complications are not uncommon among ESRD patients with PAH. Identification of those patients on transthoracic echocardiography may warrant further attention to treatment with APD.